Telaah Buku Ajar Bahasa Arab; Pendekatan Konsep 3N (Niteni, Nirokke dan Nambahi) Ki Hadjar Dewantara - Muhimmatul Choiroh; Muhammad Nashrullah (Nady Al-Adab : Jurnal Bahasa Arab, 2021)
ABSTRACT One aspect that must follow the development of an age is education, education has an important role in developing student intellectual attitudes. An alternative that can be done to develop the intellectual attitude of students is by examining the concept of the teachings of 3N in student textbooks, in this case the Arabic textbook. 3N is one of the teachings of the Tamansiswa used by Ki Hadjar Dewantara in the learning process. This article aims to examine or analyze the Arabic textbook students use a 3N approach. This research is descriptive qualitative with a type of library research then using content analysis. The results of this study are indicators of the Niteni process, Nirokke, and Nambahi in the Arabic textbook of the Madrasah Tsanawiyah class VIII of the Indonesian Ministry of Religion Mold in 2020, this shows that the Arabic textbook of the Madrasah Tsanawiyah Class VIII of the Ministry of Religion of the Republic of Indonesia in 2020 is decent used as one of the Arabic language teaching materials in school, because it has a 3N element, namely Niteni, Nirokke and Nambahi. Keywords: Niteni, Nirokke, Nambahi, and Arabic textbook